A Bibliometric Analysis of Artificial Intelligence Adoption in Business Research for the Period 2015–2025 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
Artificial Intelligence (AI) has become a transformative technology that significantly influences modern business practices, decision-making processes, and organizational innovation. As the adoption of AI continues to expand across industries, scholarly interest in this topic has increased substantially. This study aims to map the development of research on Artificial Intelligence adoption in business using a bibliometric approach. Data were collected from the Scopus database covering publications from 2015 to 2025. The analysis was conducted using VOSviewer to visualize scientific networks, including co-authorship, institutional collaboration, country collaboration, keyword co-occurrence, overlay visualization, and density mapping. The results indicate a significant growth in publications related to AI adoption in business, particularly in recent years. The United States, India, China, Germany, and Italy emerge as the most influential countries contributing to this research area, while several collaborative networks among authors and institutions highlight the global nature of this field. The keyword analysis reveals that major research themes revolve around artificial intelligence, digital transformation, technology adoption, machine learning, and decision-making processes. Additionally, emerging topics such as sustainability, ethical technology, generative artificial intelligence, and Industry 4.0 are gaining increasing attention in recent studies. This study provides a comprehensive overview of the intellectual structure and research trends in AI adoption within business research, offering insights into key contributors, major thematic clusters, and potential future research directions.